2017
DOI: 10.1111/crj.12610
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of echocardiography combined with chest CT in pulmonary hypertension

Abstract: The combination of TTE and chest CT is better than either imaging technique alone in identifying patients with PH in a heterogeneous population and may exclude PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Davarpanah et al found PAH diameter estimate (sensitivity, 88%; specificity, 78%) in the diagnosis of PAH in comparison to echo. While Shujaat et al found that sensitivity of CT in diagnosis of PAH was (75%) and specificity was (69.57%) but they compared results of CT by right heart catheter angiography (RHC) 20 .…”
Section: Our Study Revealedmentioning
confidence: 99%
“…Davarpanah et al found PAH diameter estimate (sensitivity, 88%; specificity, 78%) in the diagnosis of PAH in comparison to echo. While Shujaat et al found that sensitivity of CT in diagnosis of PAH was (75%) and specificity was (69.57%) but they compared results of CT by right heart catheter angiography (RHC) 20 .…”
Section: Our Study Revealedmentioning
confidence: 99%
“…A total of 27 articles involving 4386 subjects met our inclusion criteria (table 1). 10–13 23–45 Habash’s study was divided into two independent parts because of the differences between the case group (Habash-1) and the control group (Habash-2) 27…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 eligible studies, 14 (52%) were published between 2010 to 2019,10–13 26 27 30 33 34 39 41 43–45 and 13 (48%) were published before 2010 23–25 28 29 31 32 35–38 40 42. Twelve (44%) studies were performed in Europe,12 24 26 32–35 37–39 43 44 nine (30%) in the USA,10 13 23 25 27 28 31 40 42 two (8%) in East Asia,29 36 three (12%) in the Middle East11 41 45 and one (4%) in Australia 30. Most of the studies (15/27, 56%)11 12 23 24 28–32 35 36 38 39 41 45were of prospective design versus 44% (12/27)10 13 25–27 33 34 37 40 42–44 retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations